(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In the article the possibility of qualitative estimation of relief conditions on the basis of morphometrical data is considered. The examples received as a result of study of maps drawn up, using GIS-technologies are given. The middle quantitative data of the scale of a legend of each map were taken as favourable conditions and marked by zero, and upstream and downstream data were taken correspondingly for 1 and –1. The received data were summed up and classified into four groups and the corresponding map of complex qualitative estimation of relief conditions was drawn up.